Narrative Thinking of Healthcare Providers in Medical Cases and Its Implications for Modern Medical Education - Xiaolin YANG; Qing HUANG; Zhiheng GUO (Chinese Medicine and Culture)
Abstract. In the realm of Chinese narrative medicine, narrative thinking holds equal significance to evidence-based thinking within clinical practice, making substantial contributions to patient safety and medical quality. Ancient Chinese medical theories advocate forging a narrative bond with patients, urging healthcare practitioners to utilize Dao Shu Jie He (道术结合 integration of Dao and techniques) and Yi Dao Yu Shu (以道驭术 guiding techniques with Dao) during diagnosis, treatment, and rehabilitation. In this context, Dao (道) in traditional Chinese medicine (TCM) corresponds to narrative thinking (叙事思维) while Shu (术) aligns with scientific thinking (科学思维) in evidence-based medicine. This study adopts “narrative Chinese medicine” within the “discourse system of Chinese narrative medicine” as its framework, centering on medical stories that exemplify the application of narrative thinking in ancient Chinese diagnosis and treatment. It delves into the narrative thinking encapsulated in Chinese medicine, such as Guan Wu Qu Xiang (观物取象 observing things and extracting information), Can He Er Xing (参合而行 final examination and decision by integrating the four diagnoses), Xing Shen Bing Zhi (形神并治 body-spirit treatment), Xin Shen Jian Li (心身兼理 mind-body balance) and Bian Zheng Lun Zhi (辨证论治 treatment based on pattern differentiation). The study endeavors to inspire contemporary medical educators and clinicians to acknowledge the value of narrative thinking in TCM and fully incorporate it into daily medical practice.